PENGARUH TWITTER TERHADAP PERILAKU KECANDUAN MAHASISWA ILMU KOMUNIKASI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Nazhifah "; Nur Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Effect On Twitter Addiction Student Behaviour Science Communication Faculty Of Social And Political Science University Of Riau. Along with the development of technology, communication and information, it makes the development of the internet, that encouraging the emergence of social media. One of the social media that is popular among children now , adolescents, adults up to young people is twitter.Through 140 characters, users can change and send status updates or tweets through twitter or through applications that can be similar to twitter. Twitter is a media that can be lead the aspirations, and look at character of the crititical students, full of activities, ideas, work and opinions and expresses of the circumstances. So the twitter influences human behavior or society at this time. The purpose of this research is to determine how much influences of twitter to addiction of behavior Students Communication Faculty of Social and Political Sciences, University of Riau.The theory used in this study is the theory of CMC by Wood and Smith and social media by Andreas Kaplan and Michael Haenlein. The method used in this study is a quantitative method of explanation. Data collection techniques in this study using a questionnaire or a questionnaire. The number of samples for this study as many as 187 respondents, using a technique of random sampling. To determine how much influence these two variables, researcher used a simple linear regression analysis. As for processing the questionnaire test, is used the Statistical Product And Service Solution (SPSS) Windows version 20.Based on a simple linear regression to research the effect of twitter on addictive behavior communication science students of the Faculty of Social and Political Sciences, University of Riau, the regression coefficient values obtained in this study is Y = 2.242 + 0.434 X with a significance level of 0.000. Of course smaller than α = 0.05. It means that there are significant addiction behavior of twitter to communication science students of the Faculty of Social and Political Sciences, University of Riau by 34.5 % and 65,5 % influenced by other variables outside of the research.Keyword : Twitter, Behaviour, Addiction